(untitled) (Práxis Educativa, 2022)
The text deals with the encounters between university and school, crossed by the literature produced by black writers, with emphasis on Conceição Evaristo’s work. From interpellations presented by teachers of Basic Education in academic activities at the university, the genocide of black youth is addressed as a matter of curriculum in teacher education. In this sense, the report on the realization of a Literature Exhibition is presented, based on articulations built in the school space and at the university, mobilized by access to art. It is argued that the curricular impacts of the Exhibition go beyond the treatment of ethnic-racial issues at school as a theme, by proposing aesthetic experiences produced by the meeting. The methodological challenges in research in education is seen in a way to propose the concept of escrevivências as a theoretical-methodological operator crossed by the concepts of affect and collective agency. Keywords: Escrevivências. Black youth. Curriculum. Affect.